PROSPEK PENGEMBANGAN PERBANKAN SYARIAH PENDEKATAN PASAR - Hasan Hasan (TAHKIM, 2017)
Islamic banking can be a financial institution as well as a means of intermediation, in community economic development. Islamic banking development strategy conducted by: the expansion of Islamic banking office network in place strategies, vigorous educational programs, and dissemination of products to the community, improving the quality of service (service excellence) with the utilization of information technology access. While the prospects of development in Islamic banking market approach has been implemented with evidence; in 2014, the Islamic bank already has a network of 11 Islamic Banks (BUS), 24 Sharia Business Unit (UUS), and 155 SRB, with total office network reached 2,380 offices spread in almost all corners of the archipelago. In addition, it can be equated with the Arab countries, and Malaysia in order to four who have the potential and conducive to the development of Islamic banks. Keywords: Islamic banking, market approach